Decolonising images? The liberation script in Mozambican history textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In this article we examine the textbook narratives of the colonial past and the nation-building process in Mozambique, a Southern African country which gained its independence in 1975. One of the priorities after independence was to redesign the state apparatus and social system in order to decolonise people S minds, foster patriotism and strengthen national cohesion. We have conducted a discourse analysis of the verbal and iconic content of two Mozambican history textbooks, which are exclusively dedicated to national history: one published during the single-party or "socialist" phase; and the other published in the multi-party or "neoliberal" phase and currently in use. For this purpose, we developed an analytic framework to unveil how the textbooks' written and visual repertoires, and the combination thereof convey (or otherwise) a diverse and inclusive vision of the nation. Our findings reveal that although there have been changes in the types of language and images used, the general account of Mozambican history remains identical, emphasising the need for national unity under the leadership of the ruling political elite and recounting the History of Mozambique from the perspective of a single Liberation script, that completely overlooks the agency of women.
Keywords: Africa; Decoloniality; History education; Intersectionality; Mozambique; Nationalism